1991
DOI: 10.1111/j.1460-9568.1991.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Afferent and Efferent Connections of Temporal Association Cortex in the Rat: A Horseradish Peroxidase Study

Abstract: We studied the afferent and efferent connections of the caudal temporal cortex in rat using the tracer wheat germ agglutinin - horseradish peroxidase (WGA - HRP). This area is reciprocally connected with primary and secondary visual and auditory areas of cortex. The connections with primary visual cortex are restricted to the ventral and caudal parts of the caudal temporal area. Caudal temporal cortex has reciprocal connections with the perirhinal cortex and projects to the caudate - putamen and lateral and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
94
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 40 publications
17
94
0
1
Order By: Relevance
“…Similarly, tracing experiments in the gerbil reported a similar direct pathway between secondary visual areas and auditory cortex Schroeder and Lakatos 2009). In the rat, projections have been documented between auditory core area Te1 and primary/secondary visual areas (Vaudano et al 1991). The wide generality of cross-modal connections between low-level sensory cortices reinforces the view that they are a fundamental part of neocortical circuitry.…”
Section: Cross-species Comparisonsmentioning
confidence: 55%
See 1 more Smart Citation
“…Similarly, tracing experiments in the gerbil reported a similar direct pathway between secondary visual areas and auditory cortex Schroeder and Lakatos 2009). In the rat, projections have been documented between auditory core area Te1 and primary/secondary visual areas (Vaudano et al 1991). The wide generality of cross-modal connections between low-level sensory cortices reinforces the view that they are a fundamental part of neocortical circuitry.…”
Section: Cross-species Comparisonsmentioning
confidence: 55%
“…Recent anatomical studies have identified direct ''heteromodal'' projections between low-level putatively modality-specific auditory, visual, and somatosensory cortices (Falchier et al 2002;Rockland and Ojima 2003;Cappe and Barone 2005;De La Mothe et al 2006;Smiley et al 2007;Hall and Lomber 2008;Wang et al 2008). These findings are reproduced in a number of species including ferrets (Bizley et al 2007), gerbils (Budinger et al 2006(Budinger et al , 2008Budinger and Scheich 2009), rats (Vaudano et al 1991), and mice (Wang and Burkhalter 2007). They are augmented by a virtual explosion of physiological demonstrations of multisensory interaction in low-level cortices in a number of species, even at the level of koniocortex (reviewed by Ghazanfar and Schroeder 2006;Driver and Noesselt 2008;Schroeder et al 2008).…”
Section: Introductionmentioning
confidence: 55%
“…In addition to the direct involvement of the primary and secondary auditory cortices, the PPC receives extensive projections from the primary and secondary sensory areas (Par1, Par2), secondary occipital areas (OC2M, OC2L), and primary temporal cortex (Au1) (34). Similarly, TeA receives strong inputs from auditory cortex, as well as OC1, OC2M, and OC2L (35). ACC also receives visual (OC1, OC2M) and auditory inputs (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, TeA receives strong inputs from auditory cortex, as well as OC1, OC2M, and OC2L (35). ACC also receives visual (OC1, OC2M) and auditory inputs (35,36). RSG, besides its strong connections with hippocampus, receives extensive visual inputs (OC2M, OC2L) (34,37).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using rhyming tasks to visually presented words have shown activation in bilateral cerebellum (Fulbright et al, 1999). Although some studies show that superior portion of the cerebellum is interconnected with lateral temporal cortex (Brodal, 1978;Schmahmann & Pandya, 1991;Vaudano et al, 1991), studies in primates show that the superior portion of the cerebellar hemisphere is predominantly interconnected with inferior frontal cortex, whereas the inferior portion is predominantly interconnected with parietal cortex (Brodal, 1978;Schmahmann & Pandya, 1997). Based on the role of the inferior frontal cortex in articulation and the parietal cortex in phonological short-term memory, Desmond and colleagues proposed that superior portion of right cerebellum (VI/Crus I) is involved in articulatory control, whereas the inferior portion (VII) of right cerebellum is involved in phonological working memory (Desmond et al, 1997).…”
Section: Introductionmentioning
confidence: 99%